Biological Augmented Reality Media for Improving Deaf Students’ Understanding of the Human Immune System - Guchy Falya Maharani; Imas Diana Aprilia (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study aims to measure the effectiveness of the Biological Augmented Reality (BAR) learning media in improving understanding of the "Human Immune System" Material among deaf junior high school students. The Research employed an experimental method with a one-group pre-test-post-test design, involving six deaf students from SLB X. Participant criteria included diagnosed hearing impairments, junior high school age, basic literacy skills, and the absence of severe cognitive impairments. The procedure began with a pre-test consisting of multiple-choice questions to assess prior knowledge. Subsequently, students participated in learning sessions using BAR media, designed to present three-dimensional visualizations and interactive features to facilitate understanding of abstract concepts. A post-test was then administered to evaluate changes in students' comprehension. Data from the pre-test and post-test were analyzed using the nonparametric Wilcoxon test to identify significant differences. The results revealed a significant improvement in students' understanding after using the BAR media. The media's visualization and interactivity not only enhanced learning engagement but also helped students process information more effectively. This study recommends BAR media as an innovative learning alternative, particularly for deaf students, to address verbal communication barriers and support education.